2004
DOI: 10.1111/j.1440-1673.2004.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of intraventricular cysticercosis by magnetic resonance imaging: Improved detection with three‐dimensional spoiled gradient recalled echo sequences

Abstract: Neurocysticercosis (NCC) is caused when the cysticercus larvae of Taenia solium infect the central nervous system. The larvae usually land in the parenchymal tissue, but quite rarely can lodge in the ventricles and cisterns of the brain. Unlike parenchymal NCC, it is not easy to demonstrate the cysticercus cysts within the cerebrospinal fluid spaces. Computed tomography and even conventional MR sequences can fail to detect such cysts. However, obtaining three-dimensional spoiled gradient recalled echo imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…In pathology studies, viable cysts have a translucent membrane through which the scolex is visible as a small 2-to 3-mm nodule in the case of Cysticercus cellulosae. When the parenchymal cyst starts to degenerate, the vesicular fluid becomes opaque and dense, and the edges of the cyst become irregular and shrink 10 . The intraventricular form of NCC is more difficult to detect than the parenchymal form because the attenuation and signal intensity of the cyst's content is similar to those of CSF, and the cystic wall is usually very thin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathology studies, viable cysts have a translucent membrane through which the scolex is visible as a small 2-to 3-mm nodule in the case of Cysticercus cellulosae. When the parenchymal cyst starts to degenerate, the vesicular fluid becomes opaque and dense, and the edges of the cyst become irregular and shrink 10 . The intraventricular form of NCC is more difficult to detect than the parenchymal form because the attenuation and signal intensity of the cyst's content is similar to those of CSF, and the cystic wall is usually very thin.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have suggested that the 3D spoiled gradient recalled echo sequence (SPGR) is more accurate than spin echo T1, T2-weighted, and FLAIR images for detecting cysts and scolices in the case of intraventricular NCC 10 . SPGR is also a fast steady state acquisition, but this sequence gives T1 information.…”
Section: Neurocysticercosis: 3d Mrmentioning
confidence: 99%
“…2 Proton density images may also better delineate cysts from surrounding CSF. 5 Other sequences reported to be useful include three-dimensional (3D) spoiled gradient recalled echo (SPGR) 1 and 3D constructive interference in steady state (3D-CISS) which is a heavily T2-weighted high-resolution sequence. 2 Degenerating cysts can be detected on FLAIR and contrast-enhanced T1-weighted sequences by their increased signal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Whereas parenchymal cysticerci can be readily identified on CT and MRI, most authors agree that it is difficult to identify lesions within the cerebrospinal fluid (CSF) spaces. 1 We present a case of NCC of the 4th ventricle which was well demonstrated on conventional MRI sequences. On follow-up imaging the cyst appeared to have 'migrated' to the 3rd ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is not easy to demonstrate the parasites in some areas of the CNS. CT, and even conventional MRI, may fail to detect cysticercal cysts in the cerebrospinal fluid spaces 21 . In addition to their high cost, these sophisticated procedures are rarely available in most endemic areas of developing countries.…”
mentioning
confidence: 99%